Interlinking skies and people a "new normal" urban landscape development of Ninoy Aquino International Airport Terminal 3 - Condat, John Paul A.
Tourism in the Philippines plays an important role for the country's economy. In 2019, the Philippines catered to a volume of 11.5 million passengers (NAIA, 2019). It is evident based on the past years of increasing number of passengers, that the Philippines improves on catering a larger number of international and local tourists each year. However, in 2020, the Covid-19 pandemic happened and the number of passengers declined because of health-related restrictions set by different countries to prevent the spread of the virus. In controlling the number of passengers going in and out of the country, our airports are the first points that are subject to these restrictions greatly affecting not only our tourism and aviation industry, but also people's lives in general. Specifically in Ninoy Aquino International Airport, the number of passengers drastically decreased due to limited flights and airport capacity following the health protocols brought by the pandemic. Two years have passed, the number of passengers in airports is also slowly going back to normal wherein airport congestion is possible to take place and can cause the spread of the virus again. Hence, this thesis aims to regenerate NAIA Terminal 3's natural space as a pandemic-ready, safety-centered outdoor landscape, decongesting the terminal and giving a safe area for the airport users. Review of related literature, conduction of interviews and surveys, and data analysis of existing site elements and conditions are the methods used to come up with the basis of the landscape design. The landscape strategies used in this thesis include the reduction of Urban Heat Island (UHI) effect, Environmental Psychology, and Regenerative Landscape Techniques such as stormwater and soundscape management. Environmental Graphics Design, wayfinding, queuing management, and social distancing protocols are also utilized in the study to further improve the safety of the users. Using these strategies in the landscape design, NAIA Terminal 3 will be decongested and will provide a safety-centered outdoor space for its users while moving forward to the 'New Normal".